Program Pelita Gizi (Pendidikan Literasi Gizi) Sebagai Upaya Pencegahan Stunting Pada Bayi dan Balita Usia 0–59 Bulan di Kelurahan Sarirejo Kota Semarang - Mahmudah, Siti; Puspita, Gita Rakhma; Muna, Khafizatul; Fajriyani, Fanny Kartika (Jaanur ElBarik Indonesia, 2025)
Stunting remains a nutritional problem among children under five in Sarirejo Village, with a prevalence of 5.56% in 2025. This community service program aimed to improve nutrition literacy and prevent stunting through the